(untitled) (Research, Society and Development, 2022)
Objective: to analyze the morbidity and mortality profile of patients hospitalized for COVID-19 and discuss relevant findings in the literature. Method: This is an integrative review. A total of 538 studies were found, of which 29 were included for the review. Results: patients with higher rates of hospitalizations and deaths are male, aged over 60 years old, with chronic diseases, with the most frequent severe clinical form of the disease. COVID-19 affects pregnancy, with severe acute respiratory infections, resulting in hospitalizations and gestational interruptions. In children, the causes of hospital admissions are, in greater occurrence, nervous complications such as encephalitis and lowering of consciousness, and in the gastrointestinal system with enteropathogenic coinfections. Conclusion: this research and its results contribute to the improvement of assistance and care by health professionals.